Making Sense of Critical Pedagogy in L2 Education Through a Collaborative Study Group - Paula Andrea Echeverri Sucerquia; Sebastián Pérez Restrepo (Profile: Issues in Teachers' Professional Development)
In this article we discuss our experiences in the process of understanding critical pedagogy within an English teachers’ study group which was created for the purpose of learning how to teach language from a critical perspective. We particularly focus on the challenges of meaning making around critical pedagogy, as we realized that we were not all able to similarly enter this discourse. To illustrate our processes of understanding theory individually and collectively, some of the group members’ narratives are used as examples of our different perspectives. We argue that making sense of critical pedagogy, as part of a process of professional development, implies spaces and situations of personal confrontation with theory and support in collaborative learning through dialogue.